1982
DOI: 10.1111/j.1365-2230.1982.tb02488.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of diurnal variation in the estimation of plasma zinc

Abstract: Summary In the past there has been controversy over the existence of a significant diurnal variation of plasma zinc. For clinical use one is not only interested in the possible existence of such a varying pattern, but whether it is of sufficient magnitude that samples should be taken at standardized times of the day. Plasma zinc levels were estimated throughout the day (in a period encompassing normal laboratory working hours) in sixteen healthy male volunteers. There was a significant decrease in the mean pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…5 Other studies have shown that the meal's content and even its consistency may affect zinc concentrations. 8,12 The mean value for plasma copper concentration was significantly lower at noon as compared with the morning and afternoon values (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Other studies have shown that the meal's content and even its consistency may affect zinc concentrations. 8,12 The mean value for plasma copper concentration was significantly lower at noon as compared with the morning and afternoon values (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…It has been accepted for more than 30 years that in other species there is a significant diurnal variation in plasma zinc concentrations. 4,6,8,12,20,21 The effect of meals on the plasma zinc concentration is inconclusive. Some studies state that ingesting a meal has no effect on daily zinc concentration fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the present blood sampling was conducted early in the morning after an overnight fast, while it was done in the afternoon in the previous study. Diurnal variation in plasma or serum Zn levels has been no ticed (9)(10)(11), and P-Zn levels in the afternoon sample were about 10-20% less than in the early morning sample in our own study of subjects on an ordinary meal schedule (12). Therefore, the present P-Zn level after rectification of diurnal variation may be comparable with the previous level in female students on the average, but there remain a few female students with remarkably low values.…”
Section: Discussionmentioning
confidence: 99%